Rising Annual Costs of Dizziness Presentations to U.S. Emergency Departments. (16th July 2013) - Saber Tehrani, Ali S.; Coughlan, Diarmuid; Hsieh, Yu Hsiang; Mantokoudis, Georgios; Korley, Fredrick K.; Kerber, Kevin A.; Frick, Kevin D.; Newman‐Toker, David E.
Abstract: Objectives: Dizziness and vertigo account for roughly 4% of chief symptoms in the emergency department (ED). Little is known about the aggregate costs of ED evaluations for these patients. The authors sought to estimate the annual national costs associated with ED visits for dizziness. Methods: This cost study of adult U.S. ED visits presenting with dizziness or vertigo combined public‐use ED visit data (1995 to 2009) from the National Hospital Ambulatory Medical Care Survey (NHAMCS) and cost data (2003 to 2008) from the Medical Expenditure Panel Survey (MEPS). We calculated total visits, test utilization, and ED diagnoses from NHAMCS. Diagnosis groups were defined using the Healthcare Cost and Utilization Project's Clinical Classifications Software (HCUP‐CCS). Total visits and the proportion undergoing neuroimaging for future years were extrapolated using an autoregressive forecasting model. The average ED visit cost‐per‐diagnosis‐group from MEPS were calculated, adjusting to 2011 dollars using the Hospital Personal Health Care Expenditures price index. An overall weighted mean across the diagnostic groups was used to estimate total national costs. Year 2011 data are reported in 2011 dollars. Results: The estimated number of 2011 US ED visits for dizziness or vertigo was 3.9 million (95% confidence interval [CI] = 3.6 to 4.2 million). The proportion undergoing diagnostic imaging by computed tomography (CT), magnetic resonance imaging (MRI), or both in 2011 was estimated to be 39.9% (39.4% CT, 2.3% MRI). The mean per‐ED‐dizziness‐visit cost was $1, 004 in 2011 dollars. The total extrapolated 2011 national costs were $3.9 billion. HCUP‐CCS key diagnostic groups for those presenting with dizziness and vertigo included the following (fraction of dizziness visits, cost‐per‐ED‐visit, attributable annual national costs): otologic/vestibular (25.7%; $768; $757 million), cardiovascular (16.5%, $1, 489; $941 million), and cerebrovascular (3.1%; $1059; $127 million). Neuroimaging was estimated to account for about 12% of the total costs for dizziness visits in 2011 (CT scans $360 million, MRI scans $110 million). Conclusions: Total U.S. national costs for patients presenting with dizziness to the ED are substantial and are estimated to now exceed $4 billion per year (about 4% of total ED costs). Rising costs over time appear to reflect the rising prevalence of ED visits for dizziness and increased rates of imaging use. Future economic studies should focus on the specific breakdown of total costs, emphasizing areas of high cost and use that might be safely reduced.